Benchmarks of Diabetes Care in Men Living With Treated HIV-Infection: A Tertiary Center Experience - Fazekas-Lavu, Monika; Tonks, Katherine T. T.; Samaras, Katherine (Frontiers in Endocrinology, 2018)
Treated human immunodeficiency virus (HIV) infection is associated with high rates of type 2 diabetes mellitus (DM), metabolic syndrome and central obesity/body fat partitioning disorders. To our knowledge, there are no available data comparing diabetes care in people with both HIV+DM versus DM alone (DM-controls) within the same service and evaluating if benchmarked standards of care are being met in people with HIV+DM. This study evaluated the frequency that people with HIV+DM met the benchmarked American Diabetes Association (ADA) standards of care in diabetes (targets for HbA1c, blood pressure, lipid levels, complication screening and healthy weight), compared to age- and sex- matched controls with diabetes, in an urban teaching hospital. The frequency of diabetes complications and rates of obesity and metabolic syndrome were also examined. All participants were male; individuals with HIV+DM (n=30) were similar to DM-controls (n=30) for age, diabetes duration and smoking status, but were more frequently non-obese compared to DM controls (92% vs. 55%, respectively, p=0.003). Only 41% of HIV+DM met HbA1c targets, compared with 70% of DM-controls (p=0.037). Blood pressure targets were poorly met in both HIV+DM and DM-controls: 43% vs. 23%, respectively (p=0.12); LDL cholesterol targets were met in 65% vs. 67% (p=1.0). Benchmarked complication screening rates were similar between HIV+DM versus DM-controls for annual foot examination (53% vs. 67%, respectively, p=0.29); biennial retinal examination (83% vs. 77%, respectively, p=0.52); and annual urinary albumin measurement (77% vs. 67% respectively, p=0.39). The prevalence of diabetes complications was similar between HIV+DM compared to DM-controls: macrovascular complications were present in 23% in both groups (p=1.0); the prevalence of microvascular complications was 40% vs. 30%, respectively (p=0.51). Achieving the standard of care benchmarks for diabetes in people with both HIV-infection and diabetes is of particular importance to mitigate against the accelerated cardiometabolic outcomes observed in those with treated HIV infection. HIV+DM were less likely to achieve HbA1c targets than people with diabetes, but without HIV. People with HIV+DM may require specific strategies to ensure care benchmarks are met.